Impacts of mobile termination rates on retail prices: the implication for regulators. Issue 2 (2014) - ,; ,
Abstract : Purpose – There are only a limited number of empirical analyses on the impacts of MTRs. According to the data from 2006‐2011 by the European Regulators Group (ERG), many countries have continuously reduced their MTRs. This paper therefore aims to enrich the empirical analysis of the impacts of MTRs according to EC policy on retail prices. Design/methodology/approach – This paper applies the one‐step generalised method of moments (GMM) approach to dynamic panel data. Findings – The results support the hypothesis that lower MTRs will reduce consumer retail prices, which is consistent with the EC framework. It is therefore recommended that regulators in the calling party network pays (CPNP) regime reduce MTRs to at least the same level as the operators' cost to raise overall social welfare, especially consumer welfare. However, the approach by each country can differ depending on its situation. Originality/value – This study supports the idea that it is appropriate for the EC to regulate MTRs by reducing the rates to at least the same level as the efficient operators' cost, and other regulators with a calling party network pays regime from other regions could also follow this strategy. Acknowledgements : Received 23 November 2012 Revised 11 April 2013 Accepted 2 August 2013 The authors are grateful to Professor Teodosio Pérez Amaral, Universidad Complutense de Madrid, and Dr Christoph Stork, Research ICT Africa. This paper has greatly benefited from their constructive comments in an earlier version.